Chapter 12 NIGERIAN FILM AUDIENCES ON THE INTERNET Influences, Preferences and Contentions - Agina, Añulika (Taylor & Francis, 2022)
This handbook brings together an international team of scholars from different disciplines to reflect on African popular cultural imaginaries. These imaginaries - in the sense of cultural productions, contexts, consumers, producers, platforms, and the material, affective and discursive resources they circulate - are influential in shaping African realities. Collectively, the chapters assembled in this handbook index the genres, methods, mediums, questions and encounters that preoccupy producers, consumers and scholars of African popular cultural forms across a range of geohistorical and temporal contexts. Drawing on forms such as newspaper columns, televised English Premier League football, speculative arts, romance fiction, comedy, cinema, music and digital genres, the contributors explore the possibilities and ambiguities unleashed by the production, circulation, consumption, remediation and critique of these forms. Among the questions explored across these essays are the freedoms and constraints of popular genres; the forms of self-making, pleasure and harm that these imaginaries enable; the negotiations of multiple moral regimes in everyday life; and, inevitably, the fecund terrain of contradictions definitive of many popular forms, which variously enable and undermine world-making. An authoritative scholarly resource on popular culture in Africa, this handbook is an essential read for students and scholars of African culture, society and media.